Pengaruh Transparansi, Kompetensi, dan Partisipasi Masyarakat terhadap Akuntabilitas Pengelolaan Dana Desa pada Kantor Desa Se-Kecamatan Tirtajaya Kabupaten Karawang - Fista Apriani Sujaya; Shintarani Intan Sundari; Devi Astriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the influence of Transparency, Competence and Community Participation on the level of Accountability in Village Fund Management. Village funds are a vital resource for development at the local level and play a key role in improving the welfare of rural communities. The data used in this research is primary data based on questionnaires distributed to village officials and some to the community to obtain 150 respondents. This research uses quantitative methods, survey approaches, interviews and field observations. The sampling technique was determined using the saturated census method. This research method uses a sample of village officials who work at the Village Head Offices in Tirtajaya District, namely officials who have at least elementary/middle school education and have worked for more than one year. The choice of hypothesis testing in this study used multiple linear regression using the SMART PLS program. The main objective of this research is to explain whether the level of transparency in village fund management, competence and active community participation has a positive impact on accountability in village fund management. This research aims to provide better policy guidance in improving the efficiency and integrity of village fund management. The results of this research show that transparency, competence and community participation have a positive and significant effect on accountability in village fund management.